Prealbumin and Nutrional Assessment in Hospitalized Patients - Chaisri, Patcharaporn; Boonsiri, Patcharee; Hongsprablas, pranithi; Pisprasert, Veeradet (Archives of Allied Health Sciences, 2005)
abtract not available